Short circuit [videorecording (DVD)] - Sheedy, Ally; Guttenberg, Steve, 1958-; Stevens, Fisher; Pendleton, Austin; Bailey, G. W., 1945-; Badham, John, 1939-; Wilson, S. S. (Steven S.); Maddock, Brent, 1950- (Image Entertainment, 2000)
After a short circuit during an electrical storm, a military robot escapes and finds a home with a young woman.